1988
DOI: 10.1016/s0886-3350(88)80121-4
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of aphakic retinal detachment following intracapsular cataract extraction: A follow-up study with an analysis of risk factors

Abstract: We reviewed 604 eyes in 521 patients who had intracapsular cataract extraction. The follow-up period averaged 39 months. The incidence of rhegmatogenous aphakic retinal detachment (ARD) was 1.3% in the whole group. The ARD incidence was 1.0% in eyes without surgical complications and 5.4% in myopic eyes (myopia defined as an aphakic refraction less than or equal to +9.0 diopters). The log-rank test was used to estimate the statistical significance of various ARD predictors. Significant predictors were age at s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

1993
1993
2012
2012

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 39 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…Street & Javitt (1992) and Ninn-Pedersen & Stenevi (1995) only found this correlation for patients up to 75 years of age. However, a previous Danish study by Naeser & Kobayashi (1988) showed no association between survival and cataract extraction. No association was found by Podgor et al (1985) in a non-diabetic population, whereas diabetics with cataract showed poorer survival.…”
Section: Discussionmentioning
confidence: 73%
“…Street & Javitt (1992) and Ninn-Pedersen & Stenevi (1995) only found this correlation for patients up to 75 years of age. However, a previous Danish study by Naeser & Kobayashi (1988) showed no association between survival and cataract extraction. No association was found by Podgor et al (1985) in a non-diabetic population, whereas diabetics with cataract showed poorer survival.…”
Section: Discussionmentioning
confidence: 73%
“…The risk factors for RD were reported as myopia, young age at the time of surgery, male gender, vitreous loss and previous RD in the fellow eye. In their own study Naeser & Kobayashi (1988) observed a 1.3% incidence of RD during a 39 month risk-period after ICCE. Significant risk factors for RD were ''age below 70 at the time of surgery'' and ''myopia''.…”
Section: Discussionmentioning
confidence: 86%
“…Naeser & Kobayashi (1988) reviewed the previous literature over RD following ICCE; in papers published between 1973 and 1984 the incidence of RD among normal eyes ranged from 1.0 to 5.7%. The risk factors for RD were reported as myopia, young age at the time of surgery, male gender, vitreous loss and previous RD in the fellow eye.…”
Section: Discussionmentioning
confidence: 99%
“…2). The age groups > 70 years have previously been found to be at low risk of RD following cataract extraction (Javitt et a1 1991; Nielsen & Naeser 1993;Naeser & Kobayashi 1988;S~rensen & Baggesen 1990). This could indicate an underestimation of the incidence of RD after ECCE.…”
Section: Discussionmentioning
confidence: 96%